Extracellular matrix production by adipose-derived stem cells: Implications for heart valve tissue engineering - Colazzo, Francesca; Sarathchandra, Padmini; Smolenski, Ryszard T.; Chester, Adrian H.; Tseng, Yuan-Tsan; Czernuszka, Jan T.; Yacoub, Magdi H.; Taylor, Patricia M. (Biomaterials, 2011)
A key challenge in tissue engineering a heart valve is to reproduce the major tissue structures responsible for native valve function. Here we evaluated human adipose-derived stem cells (ADSCs) as a source of cells for heart valve tissue engineering investigating their ability to synthesize and process collagen and elastin. ADSCs were compared with human bone marrow mesenchymal stem cells (BmMSCs) and human aortic valve interstitial cells (hVICs). ADSCs and BmMSCs were stretched at 14% for 3 days and collagen synthesis determined by [ 3H]-proline incorporation. Collagen and elastin crosslinking was assessed by measuring pyridinoline and desmosine respectively, using liquid chromatography/mass spectrometry. Three-dimensional culture was obtained by seeding cells onto bovine collagen type I scaffolds for 2–20 days. Expression of matrix proteins and processing enzymes was assessed by Real Time-PCR, immunofluorescence and transmission electron microscopy. Stretch increased the incorporation of [ 3H]-proline in ADSCs and BmMSCs, however only ADSCs and hVICs upregulated COL3A1 gene. ADSCs produced collagen and elastin crosslinks. ADSCs uniformly populated collagen scaffolds after 2 days, and fibrillar-like collagen was detected after 20 days. ADSCs sense mechanical stimulation and produce and process collagen and elastin. These novel findings have important implications for the use of these cells in tissue engineering.